Kafel z wyobrażeniem Madonny z Dzieciątkiem. Z badań archeologicznych na poznańskim Ostrowie Tumskim - Gryzińska-Sawicka, Natalia; Poklewska-Koziełł, Magdalena (Ecclesia. Studia z Dziejów Wielkopolski, 2014)
The focus of the article is a stove tile with the image of the Blessed Virgin Mary and Child, discovered during archaeological works in the interior of the house of canons number 6 on the cathedral island (Ostrów Tumski) in Poznań. The authors give a brief overview of the subject matter connected with antique stove tiles found during excavations and put forward the thesis that the images on them were inspired by sculptures of the turn of the 15th and 16th century, especially the so called Beautiful Madonna sculptures. The authors also refer to other findings of stove tiles with various images of the Blessed Virgin Mary and Child from the territory of Poland. They discuss a wide range of examples of everyday religiousness and indicate that stoves built with tiles with religious motifs are manifestations of such commonplace devotion.